2015
DOI: 10.1111/wrr.12269
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent cycles of remote ischemic preconditioning augment diabetic foot ulcer healing

Abstract: The morbidity and mortality caused by diabetic foot ulcer (DFU) are still significant. Conservative treatment of DFU is often ineffective. Treatment modalities using stem cells directly into the DFU or systematically have been introduced recently. Ischemic preconditioning (IPC) has been proved to be a cheap, simple, and safe method which can augment stem cells number in the peripheral blood circulation. This study's purpose was to test whether IPC can improve DFU healing. Forty diabetic patients were enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 36 publications
(39 reference statements)
0
36
0
Order By: Relevance
“…In that study, significant protection against stroke recurrence was observed after 180 days of twice daily RIPC in symptomatic intracranial arterial stenosis patients (Meng et al 2015). Another recent study examined the impact of repeated RIPC on diabetic wound healing in patients with diabetes mellitus type 1 or type 2 (Shaked et al 2015). Patients with foot ulcers were randomized to 6 weeks of bilateral repeated RIPC (upper limbs) or a control intervention.…”
Section: Impact Of Repeated Ipc: Clinical Outcomesmentioning
confidence: 99%
“…In that study, significant protection against stroke recurrence was observed after 180 days of twice daily RIPC in symptomatic intracranial arterial stenosis patients (Meng et al 2015). Another recent study examined the impact of repeated RIPC on diabetic wound healing in patients with diabetes mellitus type 1 or type 2 (Shaked et al 2015). Patients with foot ulcers were randomized to 6 weeks of bilateral repeated RIPC (upper limbs) or a control intervention.…”
Section: Impact Of Repeated Ipc: Clinical Outcomesmentioning
confidence: 99%
“…There has been considerable variation in the timeframe of administration, ranging from one bout of 5 cycles of 5 min of ischaemia and reperfusion applied once or twice daily [43], to three 5 min cycles applied once per fortnight [44]. The period of intervention has ranged from 1 week of application of RRIC [45] to 300 days of RRIC [43].…”
Section: Potential Treatment Candidate: Ischaemic Conditioningmentioning
confidence: 99%
“…Although often termed repeat, regular or intermittent remote ischaemic pre conditioning, intervention studies utilising this method are generally applied to a chronic condition (such as heart failure [188], endothelial dysfunction [189], stroke recurrence [43] or chronic wounds [44]) or following an acute ischaemic episode (such as in a lower limb [190], post-myocardial infarction [191] or cerebrovascular accident [43]). Depending on the context, the chronicity of pathological ischaemia in the cohort, and endpoints studied, this would more accurately represent combinations of pre, per and post-conditioning, reflected in the term repeat remote ischaemic conditioning (RRIC).…”
Section: Repeat Remote Ischaemic Conditioningmentioning
confidence: 99%
See 2 more Smart Citations